PROJEKTS ERASMUS + KA2 NR.2017-1LT01-KA201-035234 "MEDIĀCIJAS SISTĒMAS ATTĪSTĪBA IZGLĪTĪBAS SEKTORĀ" - Orska, Rita; Vonoga, Aija (Education Reform: Education Content Research and Implementation Problems, 2019)
Mediation is one of the important topics in today's pedagogical science. The topicality of the project is based on educational development requirements. The main aim of the project is development of nonviolent communication skills in schools by implementing mediation system. The objectives of the project are the following: enhancing school educators' professional development through development of mediation training programme and organization of trainings; fostering pupils' conflict resolution skills through development of training programme and organization of training activities; raising awareness of mediation as effective method for nonviolent communication within school communities. Results of the project - teacher mediator preparation program; teaching material for the preparation of teacher mediators; pupil mediator preparation program; recommendations for introducing mediation in school.